Nationalism, ethnicity and the state : making and breaking nations - Coakley, John (SAGE, 2012)
Packed with a series of rich, illustrative examples, this exciting new textbook is the first to offer students a truly comprehensive AND engaging account of the vibrant topic of Nationalism.